On the Possibility of Preferred Performance Styles and Their Link to Learning Styles - Yankulov, Krassimir; Lu, Rui Ray (Frontiers in Education, 2017)
The existence of individual learnings styles is a hot topic in contemporary education theory and practice. There is an on-going debate on whether learners benefit from teaching methods that are tailored to their perceived learning styles. The majority of educators believe that such styles do exist and a striving industry benefits from this concept. However, experts conclude that the evidence on this matter provides no support for the utility of learning styles. In this manuscript we briefly review this debatable topic and focus on a key flaw in the analyses of learning styles. We indicate that the current models for the evaluation of such styles call for different instruction methods and a uniform test. However, the possibility that learner styles correlate to different performance in different types of examination has not been experimentally addressed. We discuss this discrepancy and propose methodologies that can identify such preferred performance styles.